UPAYA PENINGKATAN STRATEGI MARKETING MIX PANGAN BERBASIS BAHAN LOKAL MELALUI ANALISIS SIKAP KONSUMEN DENGAN MODEL FISHBEIN DI SURABAYA - Christina Esti Susanti (Institute of Research and Community Outreach - Petra Christian University, 2008)
This research aims to setting a contribution a thought of an exertion that should be implemented in marketing mix strategy to local material food which is discovered through an empirical research toward consumer attitude analysis by Fishbein model. The method of the research is survey, namely research which is taking population sample and setting question as an instrument of collecting the main data. The result of the research shows that: (1) by Fishbein model analysis, consumers in Surabaya appear simultaneous attitudes to the local material food that are not-agree with or not trust in package, quality, and taste to local material food especially in market Surabaya. (2) Partially consumer attitude to local material food in Surabaya by Fishbein analysis shows varies character, namely neutral, quite disagree, and disagree. (3) The efforts of marketing mix strategy of local material food in Surabaya are product strategy, price strategy, distribution strategy, and promotion strategy. Critics of this research are (1) it is necessary to set up an advanced research based on the result of the research, for example, trying to set up a research of subject more specific. (2) It is necessary to recite the research in respect to other sciences, for example, how to follow up the discovered statement that an additional foodstuff must be in fair condition.